KONSEP ZHAHIR-KHAFY DAN IMPLIKASINYA DALAM ISTINBATH HUKUM ISLAM - Romli, Romli (Universitas Islam Negeri Raden Fatah Palembang, 2018)
For further explanation given to the Prophet SAW that throughout his life every case and the problems that arise can be resolved based on the Qur'an and Sunnah. However, in subsequent periods, the community and development changes so rapidly. Islamic empire expanded and the friends were scattered to various regions along with the current expended they do. Besides active in jihad and preach, the companions also assume responsibility for leading reference Fatwa and religious information. Ibn Hazm (994 M-1086 M) is a controversial moslem scholar in the field of fiqh. One of his method of istinbat in law is zahiri. It focuses the interpretation at “nash” an the basis of the meaning at text. This method is principally similar to those used by other moslem scholars in his time. The difference is that the reasons used. In short, Ibn Hazm and other moslem scholars try to understand the religious matters an the basis of zahiri method or well-know as bayani pattern.